Effect of Customers’ Names on Brand Choices: - Taku Togawa; Yuriko Isoda; Ryo Suzuki; Naoto Onzo (Maketingu Janaru, 2023)
People perceive letters included in their name more favorably than those not included in their name. This tendency is called the name letter effect, and it can affect various types of decision-making, including brand choices. For instance, a consumer named Lundy is more likely than one named Thomas to purchase a Lexus car, as it shares the same initial. This study examines how the name letter affects consumers’ brand choices when brand names are written in Japanese Kanji script. Previous studies have shown that Kanji are processed as visual rather than auditory information. Based on this linguistic nature, the authors predicted that the name letter effect in Kanji would be elicited by congruence between a brand name and a consumer’s name in both spelling and pronunciation (vs. only in pronunciation). An analysis of actual purchase data concerned with the OTC stomach medicine Ohta-Isan (太田胃酸) revealed that consumers with names that matched the brand name (太田) in both pronunciation and Kanji spelling were more likely to purchase the medicine than consumers whose name was pronounced the same but written with different Kanji (e.g. 大田 and 多田, both pronounced Ohta) and consumers with names neither spelled nor pronounced the same way.